Building Energy Performance Simulation for Residential Structures Using EnergyPlus: A Case Study at the College of Science and Technology (CST) in Phuentsholing, Bhutan - Floralde, Karen; Janer, Susan Pura (Journal of Progress in Civil Engineering, 2025)
Energy consumption in residential building is considered to be one of the biggest areas which consume maximum energy which is a major concern currently due to unparalleled demand. Thus, this report analyses the energy performance of one of the residential buildings at CST. The study was performed on both the existing and proposed buildings, and a comparative analysis was done to accomplish the project's objectives of proposing thermal comfort for the occupants and studying overall energy usage. The analysis of the entire building was demonstrated using the EnergyPlus software applications. Likewise, the blower door test study result pointed that the building was partially exposed to the wind. Thus, by sealing the gaps, the infiltration was reduced. Furthermore, simulation of the real-time building found its energy use to be around 184,580 MJ which, by implementing the energy conservation measures such as shading and double-glazed windows with low SHGC, energy usage was reduced.